The Effectiveness of Mind Mapping to Teach Writing Procedure Text in SMPN 1 Diwek: A Pre-Experimental Study at Class IX C in SMPN 1 Diwek Jombang in The Academic Year 2022/2023 - Najiyullah, Ryan; Agustina, Ria Kamilah (English Education Study Program, 2023)
The objective of this research is to find out whether or not the use of mind mapping method effective to improve the students’ writing skill on procedure text, in terms of content, vocabulary, grammar and mechanics. The researcher conducted a pre-experimental group design. The population of this research is the ninth-grade students of SMPN 1 Diwek Jombang in the academic year 2022/2023. Total of the population was 8 classes and the total 254 students. The sample in this study was class IX C SMPN Diwek Jombang, totaling 32 students. Based on the data normality test that has been carried out by the researcher, it shows that sig. 2-tailed is 0.200 meaning that the data is normally distributed, then it will be continued with a simple paired t-test. based on the Testing of Hypothesis Terms, If the score of t is sig. <0.05, Ha is accepted and H0 is rejected. on the simple paired t-test calculation, the data shows sig. (2-tail) 0.000. The data is smaller than 0.05, meaning that H0 is rejected and Ha is accepted.